Quality Changes of Light Flesh Tuna at Water of Tomini Bay, Gorontalo Province - Wila Rumina Nento; Tati - Nurhayati; Ruddy - Suwandi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2014)
Tuna is one of the mainstay fisheries commodities that involve many of the ordinary fishermen. The handling usually still not follows the principles of good handling that causing the poor quality as the result.The aims of this research were to analyze and to determine the quality of tuna meat (the abdominal wall, dorsal fin, and caudal fin). Raw material yellowfin tuna meat prepared for the light, the meat section of the abdominal wall, dorsal fin, and caudal fin. The result of organoleptic analysis showed that the tuna meat was above the minimum value for the criteria of fresh fish. The result of TVB analysis showed that the meat on the caudal fin had the highest value and significantly different with the other, but still exist on the safe limits and on the fresh category. For the result of analysis in histamine, it shown that at the fourth hour the meat at the dorsal fin had the histamine content which were above the minimum that have been recommended. For the result of analysis in peroxide number, it shown that the tuna meat did not sustain the fat damage until the fourth hour after the catching process. And for the result of analysis in TPC, it showed that at the fourth hour the tuna meat on the pectoral fin had the highest number of total colony and significantly different with the other.Keywords: handling, histamine, light flesh, microbiology, yellowfin